2020
DOI: 10.1123/ijsnem.2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Cannabidiol Use Within Male Professional Rugby Union and League Players: A Quest for Pain Relief and Enhanced Recovery

Abstract: Rugby is characterized by frequent high-intensity collisions, resulting in muscle soreness. Players consequently seek strategies to reduce soreness and accelerate recovery, with an emerging method being cannabidiol (CBD), despite anti-doping risks. The prevalence and rationale for CBD use in rugby has not been explored; therefore, we recruited professional male players to complete a survey on CBD. Goodness of fit chi-square (χ2) was used to assess CBD use between codes and player position. Effects of age on us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 30 publications
0
42
0
6
Order By: Relevance
“…One pharmaceutical CBD product (Epidiolex®) is currently approved in Europe for the therapy of a serious form of epilepsy in children (Dravet syndrome) 13 . However, CBD products are frequently sold as nutritional supplements, novel foods, or cosmetics and can be purchased in pharmacies, organic shops, drugstores, supermarkets, and via the Internet, and a growing receptivity amongst elite athletes is conceivable 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…One pharmaceutical CBD product (Epidiolex®) is currently approved in Europe for the therapy of a serious form of epilepsy in children (Dravet syndrome) 13 . However, CBD products are frequently sold as nutritional supplements, novel foods, or cosmetics and can be purchased in pharmacies, organic shops, drugstores, supermarkets, and via the Internet, and a growing receptivity amongst elite athletes is conceivable 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…Based on its documented medical properties, the fact that it was recently legalized in many countries and removed from the list of performance-enhancing drugs prohibited by the World Anti-Doping Association, CBD is becoming increasingly popular as an over-the-counter drug for the general population and athletes. The latter seek relief of chronic pain, EIMD, or improved recovery following intense training and competition (Kasper et al, 2020;Zeiger et al, 2019). However, much of the evidence that promotes the use of CBD by athletes is anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Another population that is increasingly turning to CBD is athletes looking for recovery aids that allow a greater training load. In contact sports such as rugby, as many as 26% of players self-reported current or past use of CBD with the number reaching approximately 40% in the oldest age group, that is, between 28 and 33 years (Kasper et al, 2020). The primary reasons reported for taking CBD were relief of pain and improved recovery.…”
mentioning
confidence: 99%
“…It has been considered as non‐intoxicating and potentially (or evidently) beneficial as anti‐inflammatory, analgesic, anxiolytic, and/or neuroprotective compound, and yet the global regulatory status is complex, ranging from classifying CBD as a controlled substance to allowing for CBD products being sold as nutraceuticals 171,172 . Further, the quality of several CBD products has been questioned, especially concerning the substantial presence of other natural cannabinoids (e.g., tetrahydrocannabinol, THC, cannabigerol, and cannabichromene), all of which could cause an AAF if detected at concentrations exceeding established thresholds or reporting levels 173 ; nevertheless, recent prevalence studies demonstrated that a considerable number of study participants from sports characterized by frequent high‐impact collisions have used CBD products for improved recovery, pain, and sleep management, largely without consulting a nutritionist 174 . In order to avoid inadvertent AAFs, thorough and immediate education of athletes and their entourage is recommended, also with regards to the use of products labeled as, for example, “light cannabis.” 175 …”
Section: Corticoids and Cannabinoidsmentioning
confidence: 99%
“…171,172 Further, the quality of several CBD products has been questioned, especially concerning the substantial presence of other natural cannabinoids prevalence studies demonstrated that a considerable number of study participants from sports characterized by frequent high-impact collisions have used CBD products for improved recovery, pain, and sleep management, largely without consulting a nutritionist. 174 In order to avoid inadvertent AAFs, thorough and immediate education of athletes and their entourage is recommended, also with regards to the use of products labeled as, for example, "light cannabis." 175…”
Section: β 2 -Agonistsmentioning
confidence: 99%